THE RELATIONSHIP BETWEEN LEADERSHIP STYLE AND STUDENTACHIEVEMENT IN SCHOOLS IN ISRAEL - Ravit, Amir (E-Journal VFU, 2024)
We live in a time, in which the rate of change is faster than in any other period predatingit, in the history of humanity [2], [11]. Schools in Israel and around the world are required to functionin an intensive period of powerful changes. The needs of Man and the society change in their essenceas well as in their level of complexity [8]. Therefore, the success of an organization greatly dependsupon its ability to deliver its inherent knowledge to its clients [10]. The need for improvement of jobperformance has brought about a multitude of studies which have attempted to locate the predictorswhich explain job performance [1],[3],[6],[7].
Keywords: Job Performance (achievements); Perceived External Prestige (PEP) of the Organizational; Team; Profession; And Identity: Organizataional; Team Professional Identification; Behavioral Integration of the Team and organization; Economic educational indicators Leadership style